Preoperative CT lymph node size as a predictor of nodal metastasis in resectable Colon cancer: a retrospective study of 694 patients - Tetsuro Kawazoe; Ryota Nakanishi; Koji Ando; Yoko Zaitsu; Kensuke Kudou; Yuichiro Nakashima; Eiji Oki; Tomoharu Yoshizumi (BMC Gastroenterology)
Abstract Purpose This study aimed to investigate the efficacy of measuring lymph node size on preoperative CT imaging to predict pathological lymph node metastasis in patients with colon cancer to enhance diagnostic accuracy and improve treatment planning by establishing more reliable assessment methods for lymph node metastasis. Methods We retrospectively analyzed 1,056 patients who underwent colorectal resection at our institution between January 2004 and March 2020. From this cohort, 694 patients with resectable colon cancer were included in the study. We analyzed the relationship between lymph node size on preoperative CT imaging and lymph node metastasis identified on postoperative pathological examination. Results The optimal cutoff values for the maximum long diameter and short diameter of regional lymph nodes on preoperative CT were identified as 6.5 mm and 5.5 mm, respectively, with an AUC of 0.7794 and 0.7755, respectively. Notably, the predictive accuracy varied by tumor location. Higher cutoff values were observed in the right-sided colon (maximum long diameter: 7.7 mm, maximum short diameter: 5.9 mm) compared to the left-sided colon (maximum long diameter: 5.8 mm, maximum short diameter: 5.2 mm). Conclusion Lymph node size on preoperative CT is a significant predictor of pathological lymph node metastasis in colon cancer. Notably, the optimal cutoff values for predicting lymph node metastasis vary depending on the specific region within the colon.